Microbiological quality analysis of raw, pasteurized, UHT milk samples collected from different locations in Bangladesh (Stamford Journal of Microbiology, 2015)
Present study attempted to determine the microbiological quality of raw, pasteurized and UHT (Ultra High Temperature-processed) milk samples collected from different locations in Bangladesh. A total of 46 samples were studied including 22 raw milk samples from the local dairy markets and 24 different brands of pasteurized and ultrahigh temperature (UHT) treated milk manufactured in different beverage industries. The samples were examined for determining the total viable bacterial count (TVBC) and total coliform count (TCC). Results revealed that the raw milk samples were substandard in terms of TVBC and TCC. The range of TVBC and TCC in raw milk samples was 5.2×108 to 1.3×107 cfu/ml and 4.2×104 to 1.0×104 cfu/ml, respectively. On the contrary, the quality of pasteurized and UHT-treated milks was excellent. The TVBC range in pasteurized milk samples was from 1.8×103 to 1.1×102 cfu/ml, slightly lower than that recommended by the Bangladesh Standards and Testing Institution (BSTI). Interestingly sample numbers P-6, P-10 and P-12 of pasteurized milk samples had no growth at all both in terms of TVBC and TCC and none of the UHT processed milk contained any bacteria. So from the consumer point of view, both types of processed milk can be considered safe for consumption within the mentioned expiry date. DOI: http://dx.doi.org/10.3329/sjm.v4i1.22753 Stamford Journal of Microbiology, Vol.4(1) 2014: 5-8